Production of CFTR Mutant Gene Model by Homologous Recombination System - Hanieh Rezaee; mohammad Salehi; Mojgan Bandehpour; Sima Kalantari; Sara Hosseini; Khosrow Agin; Bahram Kazemi (Cell Journal, 2022)
Objective: The most common mutation in cystic fibrosis (CF), (ΔF508-CFTR), results in impaired protein maturation,folding and transportation to the surface of the cell. As a consequence of impaired protein maturation and/or transport from the extracellular matrix to the cell, different systems are influenced, including gastrointestinal system and glandular system, reproductive system and respiratory systems. CF models are essential tools to provide further knowledge ofCF pathophysiology. With this aim, we designed a transgenic CF model based on the homologous recombination (HR)system.Materials and Methods: In this experimental study, a specifically designed construct containing the CFTR gene with F508del was cloned into a PTZ57R cloning vector and then the construct was transformed into the male pronucleus by microinjection after in vitro fertilization (IVF). Then the rates of blastocyst formation and embryonic development at72 hours after IVF, were evaluated using the inverted microscope and the insertion of the construct was approved bypolymerase chain reaction (PCR) method.Results: The CFTR gene was successfully cloned into the PTZ57R cloning vector and overall, from 22 injected cells, 5 blastocysts were observed after pronuclear injection of the CFTR gene construct. PCR verification of the blastocyst with CFTR-specific primers represented complete recombination of CFTR into the mouse genome.Conclusion: For the first time we designed a unique genome construction that can be detected using a simple PCR method. The pronuclear injection was performed for the transformation of the genome construct into the male pronuclei using microinjection and the development of zygote to the blastocyst stage has been observed following transgenesis.